Study on the CM EMI Generation Characteristics of the Si/SiC Hybrid Switch at Different Switching Patterns and Gate Resistors - Zhu, Yong; Peng, Zishun; Dai, Yuxing; Zhao, Zhenxing; Liu, Zeng; Zheng, Zijie (Frontiers in Electronics, 2022)
The switching patterns and gate resistors of the Si/SiC hybrid switch are the key to realize its own highly efficient and reliable operation. However, as an important performance indicator, the common mode (CM) electromagnetic interference (EMI) noise caused by the Si/SiC hybrid switch is lack of the comprehensive research, which means that it is not clear how the switching patterns and gate resistors affect the CM EMI. In this paper, the Si/SiC hybrid switch based boost converter is established at first. Then, by analyzing the spectral characteristics of the CM voltage of the Si/SiC hybrid switch, the CM EMI generation characteristics of the Si/SiC hybrid switch at different switching patterns and gate resistors is revealed. And the analysis and experimental results can be used to comprehensively guide the design of gate drive pattern, gate resistors, and EMI suppression strategy.